Hot ductility behaviour of high manganese steels with varying aluminium contents. Issue 5 (24th March 2017) - Steenken, B.; Rezende, J. L. L.; Senk, D.
Abstract : The influence of aluminium on the hot ductility of high manganese steels between 700°C and Tliq has been examined, using the hot tensile test machine. Five materials with 17 wt-% [Mn], 0.3 wt-% [C] and 0–8 wt-% [Al] were cast. To detect the cause of cracking, optical microscopy and scanning electron microscopy analysis of the fracture surfaces have been conducted and compared to thermodynamic modelling. By adding more than 3 wt-% [Al] the fully austenitic structure changed to a two-phase structure (δ-Fe, γ-Fe). In case of the one- and also two-phase structured materials two regions of lower ductility (<30% RA) are present. Complex (AlN) and Mn(S, Se) precipitates were formed with different cores in dependence of the [Al] content.